Calf health and performance during receiving is not changed by fence-line preconditioning on flint hills range vs. drylot preconditioning - Bailey, E.A.; Preedy, G.W.; Pacheco, L.A.; Jaeger, John R.; Waggoner, Justin W.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Ranch-of-origin preconditioning can improve the welfare and performance of beef calves by decreasing the stress associated with weaning, transport, diet change, and commingling with other calves. Preconditioning methods that involve pasture weaning coupled with maternal contact (i.e., fence-line weaning) have been promoted as possible best management practices for minimizing stress. Prior studies focused on performance and behavior during preconditioning on the ranch of origin. Little information has been published relating to carryover effects of fence-line preconditioning compared with conventional drylot preconditioning on performance and behavior during feedlot receiving. Our objectives were to measure growth and health during a 28-day ranch-of-origin preconditioning phase and during a 60-day feedlot receiving phase among beef calves subjected to 1 of 3 ranch-of-origin preconditioning programs: (1) drylot preconditioning + dam separation, (2) pasture preconditioning + fence-line contact with dams, and (3) pasture preconditioning + fence-line contact with dams + supplemental feed delivered in a bunk. In addition, we recorded incidences of behavioral distress among these treatments during first 7 days of feedlot receiving.
Keywords: Cattle; Calf performance; Drylot preconditioning; Fence-line preconditioning